KRITIK ILMIAH DALAM PERSPEKTIF ISLAM - Hakim, Azizul (Universitas Islam Negeri Alauddin Makassar, 2021)
This paper discusses the theory of scientific criticism for the progress and development of science. Science and technology carry out a noble mission, namely for the happiness and good of mankind. In Islam it is also taught that to obtain the good of the world and the hereafter, it is necessary to have knowledge. Therefore, science must always be guarded with a view of life that is full of religious values, so that knowledge is absolutely felt for humans. In this paper, the author focuses on discussing the theory of scientific criticism in an Islamic perspective. Knowing this material is important because the key to the success of Islamic scholarship is the spirit of criticism among Islamic scientists. The main problem that the author discusses in this paper is the definition of scientific criticism in an Islamic perspective, Islamic principles and ethics of scientific criticism, and the function of scientific criticism according to Islam. The conclusion of this paper is that scientific criticism in an Islamic perspective is a response, a correction made by humans based on scientific arguments by looking at theories or practices that are in accordance with religious (Islamic) norms. The Islamic principles regarding scientific criticism are the principle of difference of opinion, ideas or ideas, the principle that criticism is based on benefit, and the principle that criticism must be voiced even though others hate it. The ethics of scientific criticism in an Islamic perspective is that criticism must be objective, rational, intended for a truth, openly expressed, and prioritize the benefit of scientists. The function of scientific criticism according to Islam is to foster critical power, foster an attitude of openness, form an open-minded attitude, and form a laughing intellectual personality.